Organic matter dynamics in distinct soil zones following ridge planting of eucalypt in Southern Brazil grasslands - Santos, Rafael Silva (2018)
The global demand for energy, fiber, and food has intensified land use of several areas worldwide, altering soil carbon (C) dynamics. Grasslands are considered strategic to mitigate climate changes due to its ability to store C on soil, but their management (e.g. ridge tillage) and native vegetation replacement may lead to net C loss to atmosphere. The Southern Brazilian grasslands (Pampa) have been largely replaced by eucalypt plantations, however the impact and magnitude on native (old; derived mostly from C4 plants) soil organic matter (SOM) destabilization and new SOM (derived from C3 eucalypt plants) formation is not clear so far. In this study, the objective was to access the initial changes in soil C and nitrogen (N) stocks in SOM fractions (particulate organic matter – POM; mineral associated organic matter – MAOM) in the ridge (row) and inter- ridge (inter-row) soil zones up to 1 m depth in the first cycle of a eucalypt plantation. We evaluated the soil changes in row and inter-row zones at different soil depths over a period of 32 months in a eucalypt stand ridge-planted in a native grassland field in Southern Brazil. The replacement of native Pampa cover by eucalypt plants reduced C and N stocks after a period of 32 months. MAOM fraction had C loss 12 times higher than that observed in the POM (0-100 cm soil depth). No changes were observed in POM-N stocks after 32 months of eucalypt planting. However, the MAOM fraction presented an annual N mineralization that reached about 780 kg ha -1 . Higher C depletion was observed in the row zone, indicating the occurrence of priming effects triggered by high fine roots density. The row zone contributed for greater net C loss, whereas larger net N mineralization were observed in the inter-row soil zone. The soil layers with the largest C saturation deficit (CSD) presented the highest new (eucalypt-derived) organic matter formation efficiency (OMFE), which varied from 12.2 to 22.4% in the row position. The grassland soils have a large potential (1.5 times more than currently) for further sequestering and stabilizing C on soil. The predominance of more active 2:1 minerals and the presence of less crystalline Fe and Al oxy(hydro)xides in the clay fraction may lead to greater C protection. These results suggest that the replacement of native Pampa biome by eucalypt stands has reduced soil organic C in the first three years and that N has been widely scavenged from more stable native SOM to sustain forest growth and new SOM formation. This fact highlights the importance of an adequate eucalypt fertilization program, particularly for N, in order to prevent a progressive impoverishment of the SOM, which in turn may undermine the production capacity of the sites in the long term.